ANALISA DAN PERANCANGAN SISTEM PENGADAAN DAN PENGENDALIAN PERSEDIAAN BAN DAN SUKU CADANG DENGAN METODE EOQ (STUDI KASUS: PT. SEMPURNA DELTA KIRANA) - Shintya Dharma Yanti; Andi Nugroho (Universitas Muria Kudus, 2021)
Procurement and inventory control is something to be considered in the company's business cycle, starting from the ordering process to inventory collection. PT. Sempurna Delta Kirana is one of the freight forwarding companies that purchase tires and spare parts regularly. As for the problems that often occur is the goods that have been ordered is not delivered on time, errors in the delivery of the type of goods, reports of entry checks and the expenditure of goods that are inaccurate and less transparent. To overcome these problems, we propose the manufacture of procurement system and control of tyre supplies and spare parts at PT. Sempurna Delta Kirana. By analyzing and designing applications of information system procurement and supply of goods using EOQ method as a method of research, pieces method as a problem analysis and prototyping method as a system development method, the results of this research is expected to provide the efficiency and effectiveness of the procurement process and control of company goods inventory. Keywords: EOQ, piesces, procurement, prototyping,reports,spareparts.